2018
DOI: 10.1158/1078-0432.ccr-17-2664
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of PD-L1+ Exosomes in Plasma of Head and Neck Cancer Patients

Abstract: Circulating PD-L1 exosomes in HNC patients' plasma but not soluble PD-L1 levels associate with disease progression. .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
495
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 520 publications
(516 citation statements)
references
References 39 publications
18
495
1
2
Order By: Relevance
“…C) The heatmap of Δ F norm values of HOLMES‐Exo PD‐L1 for PD‐L1 negative and positive exosomes at different concentrations of exosomes, and the PD‐L1 antibody for PD‐L1 positive exosomes at different concentrations of exosomes. D) Comparison of our method with previously reported methods (ELISA, FCM) indicates that our present method required less time and minimal reaction volume, and it did not require extra separation of unbound aptamers.…”
Section: Resultsmentioning
confidence: 64%
“…C) The heatmap of Δ F norm values of HOLMES‐Exo PD‐L1 for PD‐L1 negative and positive exosomes at different concentrations of exosomes, and the PD‐L1 antibody for PD‐L1 positive exosomes at different concentrations of exosomes. D) Comparison of our method with previously reported methods (ELISA, FCM) indicates that our present method required less time and minimal reaction volume, and it did not require extra separation of unbound aptamers.…”
Section: Resultsmentioning
confidence: 64%
“…Various other liquid biomarkers may provide additional diagnostic and prognostic information in HNSCC. Examples include elevated serum miR‐21, circulating PD‐L1 + exosomes, and presence of the TGFβ 1 genotype, all of which may be associated with a poorer prognosis.…”
Section: Biomarkers From Liquid Biopsiesmentioning
confidence: 99%
“…In the context of tumor‐derived exosomes, the levels of exosomal programmed death‐ligand 1 (PD‐L1) have been intensively investigated. Studies have shown that levels of exosomal PD‐L1 are associated with tumor progression in different types of malignancies such as metastatic melanoma, glioblastoma, and head and neck and breast cancers . Among various potential mechanisms, Poggio et al .…”
Section: Introductionmentioning
confidence: 99%